Genetic variation of avirulence genes (AVR‐Pi9, AVR‐Pik, AVR‐Pita1) and genetic diversity of rice blast fungus, Pyricularia oryzae, in Thailand. (5th September 2021) - Sutthiphai, Thanathip; Damchuay, Katanyutita; Neupane, Ram Chandra; Longya, Apinya; Sriwongchai, Tanee; Songkumarn, Pattavipha; Parinthawong, Nonglak; Darwell, Kulchana; Jantasuriyarat, Chatchawan
Abstract: Genetic variation of the rice blast ( Pyricularia oryzae ) population in Thailand was investigated based on the nucleotide sequence of three avirulence genes, AVR ‐ Pi9, AVR ‐ Pik, and AVR ‐ Pita1 . Sixty rice blast isolates were collected from rice‐growing areas around Thailand. Gene‐specific primers were used to amplify these AVR genes and AVR ‐ Pi9, AVR ‐ Pik, and AVR ‐ Pita1 were detected in 60, 57, and 23 isolates, respectively. Based on the AVR ‐ Pi9 sequences, we identified one rice blast isolate containing an amino acid change from glutamic acid to aspartic acid. Moreover, two rice blast isolates had identical sequences to the rice blast strain originating in Japan, indicating a potential movement of this isolate from Japan to Thailand. Three AVR ‐ Pik alleles were found, including AVR ‐ PikA (3.51%), AVR ‐ PikD (71.93%), and isolates with two copies of AVR ‐ PikD and AVR ‐ PikF (24.56%). AVR ‐ PikA and AVR ‐ PikF are virulent to Thai rice variety Jao Hom Nin. Six haplotypes of AVR ‐ Pita1 were identified with one deletion and 12 amino acid substitutions. This study revealed that different AVR genes in Thai rice blast populations have different levels of genetic variation: AVR ‐ Pi9 and AVR ‐ Pik genes have a relatively low genetic diversity, while the AVR ‐ Pita1 gene has high genetic diversity. We found AVR ‐ Pi9 was not under selection pressure, while AVR ‐ Pita1 was under purifying selection pressure. In addition, geographic location has influenced the distribution of genetic variation of AVR ‐ Pita1 . The information obtained from this study is valuable for the future development of breeding strategies for rice blast resistance in Thailand. Abstract : Genetic variation of three avirulence genes of rice blast isolates in Thailand was studied. The AVR‐Pi9 and AVR‐Pik genes have a relatively low genetic diversity, while the AVR‐Pita1 gene has a high genetic diversity.